2020
DOI: 10.3171/2019.11.spine19868
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography Hounsfield unit–based prediction of pedicle screw loosening after surgery for degenerative lumbar spine disease

Abstract: OBJECTIVEThe authors investigated the relation between Hounsfield unit (HU) values measured on CT and the risk of pedicle screw loosening in patients who underwent lumbar pedicle screw fixation for degenerative lumbar spine disease.METHODSPatients who were treated with lumbar pedicle screw fixation between July 2011 and December 2015 at the authors’ department were reviewed. Age, sex, BMI, smoking and diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 28 publications
6
69
1
1
Order By: Relevance
“…A retrospective review by Zou et al [ 10 ] studied the relationship between preoperative HU values (axial CT) and the 1-year risk of pedicle screw loosening in 503 patients that underwent lumbar pedicle screw fixation (posterolateral lumbar fusion (PLF) or posterior lumbar interbody fusion (PLIF)) due to degenerative lumbar spine disease. The mean age was 61.2 years, and 315 (62.6%) of patients were female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective review by Zou et al [ 10 ] studied the relationship between preoperative HU values (axial CT) and the 1-year risk of pedicle screw loosening in 503 patients that underwent lumbar pedicle screw fixation (posterolateral lumbar fusion (PLF) or posterior lumbar interbody fusion (PLIF)) due to degenerative lumbar spine disease. The mean age was 61.2 years, and 315 (62.6%) of patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…Another study correlated HU with successful fusion rates at least 12 weeks postoperatively, suggesting higher BMD may lead to an increased likelihood of fusion at 12 weeks [ 9 ]. Zou et al determined that a low HU value was significantly correlated as an independent factor for postoperative screw loosening in patients 1 year after lumber pedicle screw fixation for the treatment of degenerative lumbar spine disease; however, the authors also suggested other potential influencing factors, such as screw size, postoperative sagittal alignment, and other spinopelvic parameters [ 10 ]. These studies suggested that HU may be useful in both presurgical planning and postoperative outcome prediction with respect to fusion rates and screw fixation in osteopenic and osteoporotic patients undergoing LIF.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,17 Recent studies have shown that HU values measured on preoperative CT are independent predictors of implant loosening, and lower HU values are significantly correlated with a higher risk of pedicle screw loosening after lumbar fusion. [34][35][36] Schwaiger et al demonstrated that HU values on CT adequately differentiated patients with and without osteoporotic fractures, and they showed that HU values could predict pedicle screw loosening after fusion. 36 However, previous studies have focused on the lumbar spine, establishing thresholds of 135 HU for osteopenic spines, 120 HU for the risk of pedicle screw loosening, 110 HU for osteoporotic spines, and 90 HU for the risk of vertebral body fracture.…”
Section: Discussionmentioning
confidence: 99%
“…PJF, which may require revision surgery for proximal extension of fusion, was de ned as vertebral fracture of UIV or (and) UIV + 1, pull-out of instrumentation at UIV, and/or sagittal subluxation 3 . Pedicle screw loosening was de ned as the clear zone around the pedicle screw exceeded 1 mm on anteroposterior and lateral radiographs 16 .…”
Section: Data Collection and Radiographic Assessmentmentioning
confidence: 99%